Ganoderma lucidum Polysaccharide Peptide Reduces Oxidative Stress and Improves Renal Function in Patient with Cardiometabolic Syndrome - Syanindita Puspa Wardhani; Khilmi Ainun Nadliroh; Al Mazida Fauzil Aishaqeena; Fahriza Abid Sonia; Achmad Guntur Hermawan Suryo Adji; Intan Masyfufah Hanim; Rizkia Milladina Hidayatulloh; Anna Fuji Rahimah; Ardian Rizal; Peter Sugita; Ferry Sandra; Djanggan Sargowo (The Prodia Education and Research Institute (PERI), 2023)
BACKGROUND: Cardiometabolic syndrome is a risk factor for the development of diseases related to cardiovascular disease and decreased renal function. Ganoderma lucidum polysaccharide peptide (GLPP) has been reported to have anti-inflammatory and antioxidant properties. The current study was conducted to investigate the role of GLPP in inflammatory, oxidative stress and renal function markers of cardiometabolic subjects.METHODS: A randomized double-blinded perspective control trial with pre-post design was conducted. Cardiometabolic syndrome subjects were treated with placebo or GLPP for 60 days. Blood serum was collected from each subject before the first capsule consumption and one day after the last capsule consumption. Serum tumor necrosis factor (TNF)-α, high-sensitivity-C-Reactive Protein (hs-CRP) and malondialdehyde (MDA) levels were measured using enzyme-linked immunosorbent assay, while superoxide dismutase (SOD) level was measured using colorimetric assay. Serum urea and creatinine levels were measured using a clinical analyzer. The Cockroft-Gault formula was used to calculate estimated glomerular filtration rate (eGFR).RESULTS: Compared with the control group, the MDA level was significantly reduced, while the SOD level was significantly increased in the GLPP treatment group. Furthermore, serum urea and creatinine were lowered, while eGFR was increased in the GLPP treatment group.CONCLUSION: Treatment of GLPP for 60 days could be beneficial for lowering oxidative stress and improving renal function of patients with cardiometabolic syndrome.KEYWORDS: Ganoderma lucidum, cardiometabolic syndrome, inflammation, oxidative stress, renal function